GE_GERICHTE P/94/2019 vom 29. Juni 2021 - GE Cour de justice (2021)
CONTRAINTE SEXUELLE;VIOL;ACQUITTEMENT;IN DUBIO PRO REO;CONTRAINTE(DROIT PÉNAL);PEINE COMPLÉMENTAIRE;CONCOURS RÉEL;EXPULSION(DROIT PÉNAL);CAS DE RIGUEUR | CP.147; CP.139; CP.144; CP.156; CP.181; CP.183; CP.186; CP.190; CP.191; LEI.115.ala; LStup.19a